GENESIS OF THE EASTERN PARATETHYS MANGANESE ORE GIANTS: IMPACT OF EVENTS AT THE EOCENE/OLIGOCENE BOUNDARY - Varentsov I.M. (My University, 2002)
The giant Mn ore deposits of the Paratethys are located on the slopes and/or margins of deep basins. The Eocene ocean and associated basins were strongly influenced by large-scale submarine hydrothermal activity which supplied prodigious amounts of Ca, CO2, SiO2, Mn, and other components to the oceans. This caused a substantial shift in seawater composition and resulted in the deposition of carbonates as well huge amounts of Mn. The giant Mn ore deposits of the Eastern Paratethys were formed as a consequence of the Early Oligocene global transgression in shelf environments of marginal and epicontinental seas, frequently with anoxic regime of the bottom water.
Keywords: Oligocene; Eocene; Cenozoic::Paleogene::Oligocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Олигоцен; Кайнозой::Палеоген::Эоцен